Risks, benefits and survival strategies-views from female sex workers in Savannakhet, Laos - Phrasisombath Ketkesone; Faxelid Elisabeth; Sychareun Vanphanom; Thomsen Sarah (BMC, 2012)
Abstract Background Female sex workers (FSWs) are vulnerable to sexually transmitted infections (STIs) and encounter socio-economic and health problems, including STIs/HIV, unintended pregnancy and complications from unsafe abortion, stigma, violence, and drug addiction. Reducing risks associated with sex work requires an understanding of the social and cultural context in which sex workers live and work. This study aimed to explore the working environment and perceived risks among FSWs in Savannakhet province in Laos. Methods Five focus group discussions (FGDs) and seven interviews were conducted with FSWs in Kaysone Phomvihan district in Laos. Latent content analysis was used to analyze the transcribed text. Results The results revealed that the FSWs were aware of risks but they also talked about benefits related to their work. The risks were grouped into six categories: STIs/HIV, unintended pregnancy, stigma, violence, being cheated, and social and economic insecurity. The reported benefits were financial security, fulfilling social obligations, and sexual pleasure. The FSWs reported using a number of strategies to reduce risks and increase benefits. Conclusions The desire to be self-sufficient and earn as much money as possible put the FSWs in disadvantaged and vulnerable situations. Fear of financial insecurity, obligations to support one's family and the need to secure the future influenced FSWs' decisions to have safe or unsafe sex. The FSWs were, however, not only victims. They also had some control over their lives and working environment, with most viewing their work as an easy and good way of earning money.